2018
DOI: 10.1111/mms.12536
|View full text |Cite
|
Sign up to set email alerts
|

Dusky dolphin group dynamics and association patterns in Península Valdés, Argentina

Abstract: We inspected dusky dolphin (Lagenorhynchus obscurus) group dynamics in Golfo Nuevo and found differences in social organization between cold and warm seasons. Surveys were conducted onboard a research vessel, from which we collected behavioral observations and group fission‐fusion data from 2001 to 2008; we also collected photo‐identification data from 2004 to 2012. To analyze association patterns, we calculated half‐weight association index (HWI) and social differentiation (S). We conducted a Monte Carlo perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Such positive impact of nursery behavior on enlarging group size has not only been reported for the IPHDs in the eastern Taiwan Strait (Dungan et al, 2016), and also for other dolphin species such as bottlenose dolphins (Tursiops spp.) (Gibson and Mann, 2008b), dusky dolphins (Lagenorhynchus obscurus Gray, 1828) (Degrati et al, 2019), and Guiana dolphins (Sotalia guianensis) (Azevedo et al, 2005;Santos and Rosso, 2007;Emin-Lima et al, 2010). This social strategy i.e., dolphin group became larger when calves were present, could bring a variety of added benefits such as enhanced calf-assistance, cooperative calf-caring, reduced maternal investments, and increased calf-protection (against predators or intraspecific aggression) (Mann et al, 2000;Gibson and Mann, 2008a;Kent et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such positive impact of nursery behavior on enlarging group size has not only been reported for the IPHDs in the eastern Taiwan Strait (Dungan et al, 2016), and also for other dolphin species such as bottlenose dolphins (Tursiops spp.) (Gibson and Mann, 2008b), dusky dolphins (Lagenorhynchus obscurus Gray, 1828) (Degrati et al, 2019), and Guiana dolphins (Sotalia guianensis) (Azevedo et al, 2005;Santos and Rosso, 2007;Emin-Lima et al, 2010). This social strategy i.e., dolphin group became larger when calves were present, could bring a variety of added benefits such as enhanced calf-assistance, cooperative calf-caring, reduced maternal investments, and increased calf-protection (against predators or intraspecific aggression) (Mann et al, 2000;Gibson and Mann, 2008a;Kent et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This increase in feeding, traveling, or socializing group size has been reported for the bottlenose dolphins (Heithaus and Dill, 2002), common dolphins (Delphinus spp.) (Neumann, 2001;Stockin et al, 2009), and dusky dolphins (Degrati et al, 2019). IPHDs tended to form large, temporary, and functional gathering of different social units when they were not resting or milling (Würsig et al, 2016), which might help strengthen group added benefits (Baird and Dill, 1996;Neumann, 2001;Yeater et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In common bottlenose dolphins (T. truncatus), for example, reported values range from 0.29 in Bahia San Antonio (Vermeulen, 2018) to 1.08 in the northern Adriatic Sea (Genov et al, 2019). Some studies have also reported variations within populations between seasons, such as dusky dolphins (Lagenorhynchus obscurus) in Golfo Nuevo, where social differentiation is considerably higher during the winter (Degrati et al, 2018).…”
Section: Community Structure and Social Differentiationmentioning
confidence: 99%
“…Only adult and juvenile dolphins with a pattern of nicks and notches along the trailing edge of a dorsal fin to allow future No. biopsied dolphins --5 ( 2) 4 ( 1) 20 ( 7) 2 ( 1) 5 (3) -17 ( 6) 3 (1) 14 ( 7) 13 (2) ---re-identification were included in the photo-identification data set (Degrati et al, 2019b).…”
Section: Boat Surveysmentioning
confidence: 99%